Penerapan Model Problem Based Learning Berbasis Berdiferensiasi berdasarkan Gaya Belajar Peserta didik pada Pelajaran Biologi Materi Ekosistem Kelas X SMA - Irfiani Shafira; Fifi Fatmawati Rahayu; Fatihatunnisa Ridha Rahman; Julia Mawarni; Dian Fitriani (Departement of Mathematics Education, 2023)
This study aims to apply the Differentiated Problem Based Learning (PBL) model in Biology learning Ecosystem material by considering students' learning styles. PBL is a learner-centered learning approach and involves students to be active in the process of solving problems through investigation and collaboration between students. This research was conducted using a qualitative descriptive research method in class X at a high school in Serang City. Data on students' learning styles were collected using observation techniques through questionnaires. The results showed that there was a diversity of student learning styles, with most students identifying visual learning styles. In addition, the application of differentiation-based PBL has a positive impact because it can express potential according to their interests so as to provide a more meaningful learning experience for them.